Evaluating the genotoxicity of salinity stress and secondary products gene manipulation in lime, Citrus aurantifolia, plants - Darwish, Hadeer; Al-Osaimi, Ghaida S.; Al Kashgry, Najla Amin T.; Sonbol, Hana; Alayafi, Aisha A. M.; Alabdallah, Nadiyah M.; Al-Humaid, Abdulrahman; Al-Harbi, Nadi Awad; Al-Qahtani, Salem Mesfir; Abbas, Zahid Khorshid; Darwish, Doaa Bahaa Eldin; Ibrahim, Mohamed F. M.; et al. (Frontiers in Plant Science, 2023)
Salinity is a significant abiotic stress that has a profound effect on growth, the content of secondary products, and the genotoxicity of cells. Lime, Citrus aurantifolia, is a popular plant belonging to the family Rutaceae. The interest in cultivating this plant is due to the importance of its volatile oil, which is included in many pharmaceutical industries, but C. aurantifolia plants are affected by the NaCl salinity levels. In the present study, a comet assay test has been applied to evaluate the genotoxic impact of salinity at 0, 50, 100, and 200 mM of NaCl on C. aurantifolia tissue-cultured plants. Furthermore, terpene gene expression was investigated using a semi-quantitative real-time polymerase chain reaction. Results from the two analyses revealed that 200 mM of NaCl stress resulted in high levels of severe damage to the C. aurantifolia plants’ DNA tail 21.8%, tail length 6.56 µm, and tail moment 3.19 Unit. The relative highest expression of RtHK and TAT genes was 2.08, and 1.693, respectively, when plants were exposed to 200 mM of NaCl, whereas pv4CL2RT expressed 1.50 in plants subjected to 100 mM of NaCl. The accumulation of transcripts for the RTMYB was 0.951 when plants were treated with NaCl at 50 mM, and RtGPPS gene was significantly decreased to 0.446 during saline exposure at 100 mM. We conclude that the comet assay test offers an appropriate tool to detect DNA damage as well as RtHK, TAT, and pv4CL2RT genes having post-transcriptional regulation in C. aurantifolia plant cells under salinity stress. Future studies are needed to assess the application of gene expression and comet assay technologies using another set of genes that show vulnerability to different stresses on lime and other plants.